Socio-demographic determinants of subfertility in Sri Lanka - Wijesinghe, Dilhani (My University, 2012)
Though many couples expect children after marriage, a significant proportion of them (approximately 8% -10%) are worried over their inability to have children even after several years of married life. The incidence of subfertility in a population has important demographic and health implications as it directly affects the country’s overall fertility, and the psychological wellbeing of these couples. Previous research has focused on the medical aspects of infertility but has rarely examined the socio-demographic determinants. Therefore, this study examines the socio-demographic determinants of subfertility in Sri Lanka. The data for this study was obtained from a primary survey which was conducted in three subfertility clinics namely, Family Health Bureau, De Zoysa Maternity Hospital and Vindana Reproductive Health Center. The sample consisted of 150 subfertile couples who approach clinics for treatment and a systematic sampling method was used to select respondents. An interviewer administered questionnaire was used to collect data. The findings revealed that the prevalence of primary subfertility among couples is higher than the prevalence of secondary subfertility. Both male and female factors are associated with the subfertility. It was found that demographic factors such as the age of the woman, age at marriage, sexual intercourse within the fertile period and irregular menstruation have a significant influence on subfertility. In addition, health related factors such as reproductive system related problems, usage of long term drugs, body mass index, genetic factors and mental illnesses have affected fertility. Furthermore, socio economic factors such as education, occupation, daily working hours, location of work place, income and expenditure status have shown up as significant determinants of subfertility in Sri Lanka. These findings suggest the importance of technological advances to provide better solutions to the subfertility issues in order to minimize the prevalence of subfertility in Sri Lanka.